Karakteristik Fisik Dan Uji Mikrobiologi Serta Skrining Fitokimia Loloh Kombinasi Daun Jempiring, Daun Pegagan, Daun Katuk, Dan Air Kelapa - Puspawati, Made; Sanjaya, Dwi Arymbhi; Mendra, Ni Nyoman Yudianti (Usadha, 2025)
Loloh is a traditional herbal beverage specifically produced by the Balinese community to prevent and treat various ailments. One example of loloh used for health maintenance can be formulated from a mixture of jempiring leaves (Gardenia jasminoides), pegagan leaves (Centella asiatica), katuk leaves (Breynia androgyna), and coconut water (Cocos nucifera). A major challenge in loloh production is the risk of microbial contamination. This study aims to examine the physical characteristics, bioactive compound profile, and microbiological quality of loloh formulated from a combination of jempiring leaves (G. jasminoides), pegagan leaves (C. asiatica), katuk leaves (B. androgyna), and coconut water (C. nucifera). The research employed an experimental design with a descriptive approach. Observed variables included organoleptic characteristics (color, form, odor), pH, microbiological parameters (total plate count [TPC] and yeast and mold count [YMC]), and phytochemical screening of the loloh preparation. The samples used in this study were loloh packaged in 250 ml bottles. A total of six bottles were used, with five allocated for microbiological testing and one for phytochemical screening. The resulting loloh exhibited a brown color, a distinctive odor, and a pH of 6. All five microbiological samples showed microbial contamination exceeding the permissible limits, with TPC values surpassing 10⁶ CFU/g and YMC values exceeding 10⁴ CFU/g. Phytochemical screening revealed the presence of alkaloids, flavonoids, saponins, tannins, and steroids. It can be concluded that loloh is rich in bioactive compounds; however, hygienic practices and microbiological safety must be carefully considered, particularly during production and packaging processes.